Reciprocal images of Portuguese and Turkish university students: minding intercultural gaps in foreign language and culture education - Basílio, Daniel (2017)
Assuming that Foreign Language Education (FLE) should partake in the promotion of intercultural dialogue between two cultural realities which seem to be growing more and more incommensurable – the so called “Western Christian world” and “Eastern Muslim world” –, this study presents a diagnosis of the reciprocal images of Portuguese and Turkish university students learning each other’s language. It focuses on how these images relate to the subjects’ motivational orientations towards choosing and learning their counterpart’s language and on their readiness to establish and develop intercultural contacts and relations with speakers of that language. The study overall results show a clear imbalance between the images shared by each group : the Turkish revealing a high sense of “shared identities” between the two countries, cultures and peoples, and the Portuguese exhibiting a propensity towards their “othering”, strongly rooted in a prejudiced representation of Islam. On this basis, we propose a set of FLE strategies, aiming at the positive (re/de)construction of the students’ images, and the concomitant development of their intercultural competence.